Knowledge on health hazards associated with the consumption of carbonated soft drinks among undergraduates of University of Jaffna - Mohamed Sirajudeen, A.H.; Mahesh Nuwan Sandeepa, T.M.; Kamalarupan, L.; Kajenthini, K. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka, 2023)
Introduction: Carbonated soft drink consumption is most common among the youngest population worldwide. These beverages posed many health hazards, especially non-communicable disease. However, the youngest population consumes more without awareness of the health hazard of carbonated soft drink consumption. Objective: To determine the knowledge on health hazards of consumption of carbonated soft drinks among undergraduate students at the University of Jaffna. Methodology: Institutional based descriptive cross-sectional study was carried out among the undergraduates of Jaffna University. There were 423 students recruited as study participants from selected faculties of the University of Jaffna via a proportionate random sampling technique. A self-administered questionnaire was administered to collect the data. Data were analyzed by using SPSS version 25 and presented with descriptive statistics of mean, SD, percentages. Ethical approval was obtained from ERC, Faculty of Medicine, University of Jaffna. Results: The age of the participant varied from 22 to 27 years old with a mean age of 24.35 (SD = 0.896) years. Majority of the participants were from the faculty of arts. Majority of the students knew that carbonated soft drinks contain poor nutritive value (72.8%). However, nearly 50% of them believed that it is a high-calorie drink. Many of them were aware that soft beverages have poor protein (96.2%) and mineral (94.6%) contents. The majority of them agreed that prolonged consumption of carbonated soft drinks posed the greatest health risks of obesity (80.4%) and diabetic mellitus (80.4%). More than half of the participants reported that hyperacidity (64.5%), nausea (61.0%), and sleep disturbances (52.5%) are the most common acute effects of the consumption of the carbonated soft drink. More than half of the participants (61.2%) were aware there is a colour code indication on the carbonated soft drinks labels. The available colors in the code mentioned by the participants were red (61.2%), orange (44.4%), and green (41.8%). Many are unaware of the sugar value in grams which represents each colour code and the safest level of consumption of soft drinks in a day (91.5%). Conclusion: Nearly half of the participants had good knowledge regarding carbonated soft drinks.
Keywords: Knowledge; Health hazard; Carbonated soft drinks